2018
DOI: 10.3390/nu10111607
|View full text |Cite
|
Sign up to set email alerts
|

Low Salivary Amylase Gene (AMY1) Copy Number Is Associated with Obesity and Gut Prevotella Abundance in Mexican Children and Adults

Abstract: Genome-wide association studies (GWAS) have identified copy number variants (CNVs) associated with obesity in chromosomal regions 1p31.1, 10q11.22, 11q11, 16p12.3, and recently 1p21.1, which contains the salivary amylase gene (AMY1). Recent evidence suggests this enzyme may influence gut microbiota composition through carbohydrate (mainly starch) degradation. The role of these CNVs in obesity has been scarcely explored in the Latino population, and thus the aim of our study was to evaluate the association of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 57 publications
(89 reference statements)
0
38
2
2
Order By: Relevance
“…Although we had the same division for the low AMY1 group, their high AMY1 group included only participants with ≥8 copy numbers. As overweight/obese subjects have lower AMY1 copy numbers, [ 2,6,8 ] this could explain the lower median observed in our population.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although we had the same division for the low AMY1 group, their high AMY1 group included only participants with ≥8 copy numbers. As overweight/obese subjects have lower AMY1 copy numbers, [ 2,6,8 ] this could explain the lower median observed in our population.…”
Section: Discussionmentioning
confidence: 84%
“…[ 2,4 ] Hence, reduced AMY1 copy numbers have also been associated with increased body mass index (BMI), obesity and cardiovascular risk, IR, and inflammation in both adults and children. [ 2–8 ] However, the association between the AMY1 copy number and obesity has been challenged by recent studies that have found no significant associations despite having a strong statistical power. [ 9–12 ] These conflicting results could be partially attributed to differences in the starch intake.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The genetic connection between AMY1 CNV and obesity showed that low AMY1 copy number significantly associated with high BMI. 4,5,[11][12][13] Recently from our lab, we showed the inverse association of AMY1 copy number and the obesity measurement in children. 13 Falchi et al first reported the association of AMY1 CNV and the high risk of obesity in a longitudinal study.…”
Section: Introductionmentioning
confidence: 95%
“…body mass index (BMI) and waist circumference 7,[12][13][14][15][16][17][18][19][20][21] . However, other studies reported no association [22][23][24] or a positive association between AMY1 gene CN and BMI 25 .…”
mentioning
confidence: 99%